Precision enhanced electrochemical jet processing. Issue 1 (2018) - Clare, Adam T.; Speidel, Alistair; Bisterov, Ivan; Jackson-Crisp, Alexander; Mitchell-Smith, Jonathon
Abstract: Through electro-physical modification of the electrode gap in electrochemical jet techniques, precision has been shown to be greatly increased. Repeatable kerf widths approaching the diameter of the nozzle are demonstrated and the individual contributing effects are quantified across energy density and length scales. This allows the feature resolution achievable through electrochemical jet processing to be comparable to other surface structuring techniques, albeit with zero thermal loading of the surface. This is applied to demonstrate the machining of complex geometric features, not previously produced by electrolyte jet techniques.